KEPEMIMPINAN BERDASARKAN GENDER: EFEKTIVITAS & TANTANGAN (Studi Kasus pada Kelurahan Mugassari dan Kecamatan Tembalang) - Dwi Putranto, Indra; Perdhana, Mirwan Surya (Diponegoro Journal of Management, 2018)
Gender is not only about type of sex, but it is more about character, social role and identity in the society. Gender equality has not perfectly happened in workplace and also political issue. It caused of the incredulity of people about women leadership. However, in previous research we found that women and men are equal on their leadership capability. Therefore, this research aimed to identify leadership style, leadership effectiveness, and also challenges of men and women leaders in Indonesia.This research used qualitative method and case study approach. The main object of this research are men and women leaders in Indonesian government organizations. Moreover, this research investigated on subordinate, counterpart, and superior about leadership of those leaders.The result of this research revealed that men and women leaders are using transformational leadership style. And then, those leaders are considered equal on leadership effectiveness, and also have common challenges on task, communication, and their leadership